Cultural Transformation: An Exploration of Sudha Murty’s Portrayal of Tradition and Modernity in Select Non-Fiction - Vinil Rohan D’Souza; Srinivas Voordi, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Cultural transformation refers to the process of change and evolution in a society’s culture, values, practices, and beliefs. It is an ongoing process where cultural elements get adapted, merged, or sometimes clashed with new ideas or thoughts. This process of transformation is determined by factors like social movements, education, migration, technological advancement, globalization, etc., which influence modifications in societal attitudes, behaviors, and identities. Literature works as a mirror of cultural transformation. It captures the significant changes in the society’s beliefs, norms, values, and practices, etc. It always enables the transfer of ideas between cultures, which would lead to new cultural forms and identities. Literature often retains the core essence of culture as it evolves, bridging the cultural gaps for positive growth and prosperity. Sudha Murty’s writings explore the themes of cultural transformation, showcasing the blending of traditional Indian values with modern influences and also highlighting the interplay between tradition and modernity in Indian society. Murty in her writing captures the crux of change where tradition and culture meet progress, and humanity succeeds. Her stories aren’t simply about Indian cultural transformation; they are about the universal journey of stabilizing roots and growth. Through her perspective, we see cultural transformation not as a confrontation but as a harmonious blend of old and new.
Keywords: Sudha Murty; process of change and evolution; societal attitudes; new cultural forms; harmonious blend